2014
DOI: 10.3389/fphys.2014.00002
|View full text |Cite
|
Sign up to set email alerts
|

Potential applications of nanotechnology for the diagnosis and treatment of pancreatic cancer

Abstract: Despite improvements in our understanding of pancreatic cancer and the emerging concept of personalized medicine for the treatment of this disease, it is still the fourth most common cause of cancer death in the western world. It is established that pancreatic cancer is a highly heterogeneous disease with a complex tumor microenvironment. Indeed the extensive stroma surrounding the cancer cells has been shown to be important in promoting tumor growth and metastases, as well as sequestering chemotherapeutic age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 86 publications
(146 reference statements)
0
46
0
Order By: Relevance
“…We demonstrated that HA-conjugated liposomes received higher cell-to-CD44 expression in pancreatic adenocarcinoma than unconjugated liposomes [12].…”
Section: Hyaluronic Acidmentioning
confidence: 92%
See 2 more Smart Citations
“…We demonstrated that HA-conjugated liposomes received higher cell-to-CD44 expression in pancreatic adenocarcinoma than unconjugated liposomes [12].…”
Section: Hyaluronic Acidmentioning
confidence: 92%
“…This review shows that anti-CA199 cys-diabody providing exact molecular imaging in cancer xenograft models demonstrates target binding of pancreatic tumor cells with distributing good treatment to the target site [12,37]. Improvement in the five years survival rate of the pancreatic ductal adenocarcinoma (PDAC) quickly required.…”
Section: Immuno-liposome Based Targeted Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, most tumors are detectable only when they reach a certain size and contain millions of cells that may have already metastasized (transfer of disease from one organ or part of the body to another not directly (SPION) have been reconnoitered as potential contrast agents for cancer imaging. In more advanced development in cancer imaging, nanotechnology promises to improvise the current existing imaging platforms such as endoscopic ultrasonography (EUS) or MRI cholangiopancreatography (MRCP) for pancreatic cancer imaging of pancreatic cancer [6,7]. Nanotechnology also offers tremendous opportunities in diagnosis of cervical cancer compared to commonly used techniques of cytology and HPV detection, which are challenged due to the lack of sensitivity, especially in detecting pre-invasive cervical cancers.…”
Section: Currently Inorganic Nanomaterials Including Gold Nanoparticmentioning
confidence: 99%
“…While not covered in this review, McCarroll et al extensively evaluates how nanoformulations can improve contrast agents and in turn outcomes. [14] 1.2 Pathophysiology of the tumor PDAC is a solid tumor that is unique for its intricate stroma that makes up most of its mass. The stroma is composed of myofibroblasts, endothelial cells, pericytes, and immune cells along with its extracellular matrix (ECM).…”
Section: Established Risk Factors and High Risk Of Recurrencementioning
confidence: 99%